Paper 26: Defining Clinically Significant Improvement on Patient-Reported Outcomes Measurement Information System Test for Patients Undergoing Hip Arthroscopy for the Treatment of Femoroacetabular Impingement Syndrome at 1-Year Follow-Up. Issue 5 (31st May 2022) - Clapp, Ian; DeFroda, Steven; Newhouse, Alexander; Alter, Thomas; Nwachukwu, Ben; Nho, Shane; Bodendorfer, Blake
Objectives: While minimal clinically important difference (MCID), patient acceptable symptomatic state (PASS), and substantial clinical benefit (SCB) have been defined for hip-specific legacy patient reported outcome measures, they have not been defined for the Patient-Reported Outcomes Measurement Information System (PROMIS) instruments for patients undergoing hip arthroscopy. The purpose of the study was to define the MCID, PASS, and SCB thresholds for the PROMIS Physical Function (PF) computerized adaptive test (CAT) and PROMIS Pain Interference (PI) instruments in patients undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS). Methods: Patients undergoing primary hip arthroscopy between August 2018 and January 2019 for the treatment of FAIS were retrospectively analyzed. Patients received PROMIS-PF, PROMIS-PI, Hip Outcome Score Activities of Daily Living, Hip Outcome Score Sport Subscale, modified Harris Hip Score, and international Hip Outcome Tool-12 preoperatively and at 1 year postoperatively. MCID was calculated using the distribution method, while PASS and SCB were calculated using an anchor-based method. Patients achieving clinically significant outcomes (CSOs) were compared to those who failed to achieve via chi-square and independent sample t-tests, and a multivariate logistic regression was conducted to determine predictors of CSO achievement. Results: 124 patients with an average age of 32.7±12.3 were included in the analysis. The threshold scores required to achieve MCID, PASS, and SCB, respectively, were as follows: PROMIS-PI (-3.1, 53.7, 51.9) and PROMIS-PF (3.3, 47.0, 49.9). Patients achieved any MCID, PASS, and SCB for PROMIS scores at a rate of 89.0%, 71.8%, and 62.1%, respectively compared to 87.1%, 76.6%, and 71.8% for legacy PROMs. For PROMIS-PF, higher preoperative PROMIS-PF score was a positive predictor of CSO achievement, and patients achieving SCB were significantly younger (30.3±12 vs 35.6±12, p=0.017) with significantly lower BMIs (24.7±6.4 vs. 27.9±7, p=0.009). Preoperative chronic pain and past history of orthopaedic surgery were negative predictors of PROMIS-PI CSO achievement while higher (worse) preoperative PROMIS-PI scores were a positive predictor. Conclusions: Our study defined the MCID, PASS, and SCB for the PROMIS PF and PI CAT at 1-year postoperatively. CSO is achieved via PROMIS at a rate comparable, but slightly less than legacy hip PROMs. In addition, patients with higher preoperative PROMIS scores, younger age, and lower BMIs were more likely to achieve a CSO while preoperative chronic pain and past history of orthopaedic surgery were negative predictors of CSO achievement.